2023
DOI: 10.3389/feart.2023.1094434
|View full text |Cite
|
Sign up to set email alerts
|

A method for evaluating resource potential and oil mobility in liquid-rich shale plays—An example from upper Devonian Duvernay formation of the Western Canada Sedimentary Basin

Abstract: This paper discusses methods of assessing oil and gas resources and evaluating their mobility in shale reservoirs using programed pyrolysis data in conjunction with reservoir engineering parameters derived from production data. The hydrocarbon resource is calculated from the measured free hydrocarbon by programed pyrolysis with correction of evaporative loss that occurred during coring, storage and sample preparation. The correction takes account of the loss of light hydrocarbon fluids as a result of phase cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 47 publications
1
9
0
Order By: Relevance
“…Previous researches indicated that clay mineral pores were mainly formed from the primary pores between clay minerals due to compaction, diagenesis, and mineral alteration. Therefore, the higher the clay mineral content is, the more developed the clay mineral pores (Chen et al 2019b). Compared with marine shale, the higher clay mineral content in terrestrial shale was the main reason for the more developed inorganic pores (Liu et al 2019).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous researches indicated that clay mineral pores were mainly formed from the primary pores between clay minerals due to compaction, diagenesis, and mineral alteration. Therefore, the higher the clay mineral content is, the more developed the clay mineral pores (Chen et al 2019b). Compared with marine shale, the higher clay mineral content in terrestrial shale was the main reason for the more developed inorganic pores (Liu et al 2019).…”
Section: Resultsmentioning
confidence: 99%
“…Organic matter maturity. OM maturity determined the thermal evolution degree in source rock, and whether it was given priority to generate oil or gas, it was very important for evaluating the hydrocarbon generation potential (Chen et al 2019a;Passey et al 2010). Vitrinite reflectance (R o ) was currently the most effective indicator for determining OM maturity.…”
Section: Organic Geochemical Propertiesmentioning
confidence: 99%
“…Therefore, calibration of the lost light hydrocarbons is required. This study calibrated light hydrocarbons using the light hydrocarbon calibration model based on the phase equilibrium principle and laboratory test results of light hydrocarbon losses (Chen et al, 2019). The total light hydrocarbon loss (S L ) includes the light hydrocarbon loss (S LS ) in the sampling process and the light hydrocarbon loss (S LP ) during the sample preservation and preparation process (Equation ).…”
Section: Methodsmentioning
confidence: 99%
“…S LS is calculated by the formation volume factor (FVF) of crude oil (Equation ), while S LP is calculated from an average value of 15% obtained from light hydrocarbon loss experimental results. Therefore, the calibrated total free hydrocarbon (S 1c ) can be expressed in Equation (Chen et al, 2019). SL=SitalicLS+SitalicLP, SitalicLC=FVFS1ρoilRρoilS, S1C=S11+FVF+0.15, where, ρ oilS has a density of kg/m 3 , while ρ oilR has a density of kg/m 3 under surface conditions.…”
Section: Methodsmentioning
confidence: 99%
“…Additionally, research shows that the hydrocarbons that are difficult to volatilize before 300°C in S2 are mainly heavy components, which are considered adsorbed hydrocarbons of shale (Jarvie, 2012b;Chen et al, 2019). Adsorbed hydrocarbons are a part of the total hydrocarbon content in shale and are mainly adsorbed on the organic matter surface Zou et al, 2013;Jiang et al, 2016).…”
mentioning
confidence: 99%